2014
DOI: 10.1007/s10461-014-0695-1
|View full text |Cite
|
Sign up to set email alerts
|

Advancing the Prevention Agenda for HIV and Other Sexually Transmitted Infections in South China: Social Science Research to Inform Effective Public Health Interventions

Abstract: Despite widespread biomedical advances in treatment, HIV and other sexually transmitted infections (STI) continue to affect a large portion of the world's population. The profoundly social nature of behaviorally driven epidemics and disparities across socioeconomic divides in the distribution of HIV/STI and care outcomes emphasize the need for innovative, multilevel interventions. Interdisciplinary approaches to HIV/STI control are needed to combine insights from the social and biological sciences and public h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 108 publications
(108 reference statements)
0
2
0
1
Order By: Relevance
“…It is possibly that these findings are related to indications of greater use of governmental programs that distributed free condoms, provided educational materials and lessons, and peer support. Previous research has indicated that FSW in China are reporting higher rates of consistent condom use and HIV testing, [ 13 , 30 ] and that these rates have both be improved through the use of behavioral interventions [ 13 , 31 ]. Future studies need to more specifically examine the impact of these governmental programs by examining evaluation data that has been collected during those efforts.…”
Section: Discussionmentioning
confidence: 99%
“…It is possibly that these findings are related to indications of greater use of governmental programs that distributed free condoms, provided educational materials and lessons, and peer support. Previous research has indicated that FSW in China are reporting higher rates of consistent condom use and HIV testing, [ 13 , 30 ] and that these rates have both be improved through the use of behavioral interventions [ 13 , 31 ]. Future studies need to more specifically examine the impact of these governmental programs by examining evaluation data that has been collected during those efforts.…”
Section: Discussionmentioning
confidence: 99%
“…A presença de um psicólogo e/ou assistente social demonstrou importante diferença no acompanhamento, uma vez que fomenta a análise do comportamento sexual mantendo vida sexualmente ativa e saudável para si e para os parceiros. Esse acompanhamento promove o bem-estar da saúde mental dos infectados, bem como elucida, aos não-infectados, acerca da doença (MUESSIG, 2014).…”
Section: Intervenção Multidisciplinar Na Prevenção De Hivunclassified
“…More social science research on community perspectives, particularly on risk perception and prevention of STIs, is urgently needed, as STI treatment and care needs to be adapted to needs pertaining to rising incidences of resistances both to antiretroviral therapy (ART) and antibiotics. Increasing the role and visibility of in-depth studies would allow analysis of the intricate entanglement of challenges on structural and communicative levels and would help to adjust interventions to individual and community needs [ 10 ].…”
mentioning
confidence: 99%